Insights into the effect of surface coordination on the structure and properties of Au13Cu2 nanoclusters. Issue 41 (22nd July 2019) - Zhou, Chuanjun; Li, Hao; Song, Yongbo; Ke, Feng; Xu, Wen Wu; Zhu, Manzhou
Abstract : Changing the coordination mode from Cu–N to Cu–S significantly modulates the electronic structure of Au13 Cu2 nanoclusters. Abstract : Comparable systems are of great significance for understanding the structure–property relationship. Herein, a new Au13 Cu2 nanocluster protected by phenylethanethiol (PET) and triphenylphosphine (TPP) is synthesized and structurally determined, including an icosahedral Au13 and two CuS3 configurations. Based on previous work, a comparable system was formed—only the surface coordination of Cu atoms changes from Cu–N to Cu–S, which results in a tremendous change in the optical properties. Based on this, the effect of the coordination mode on the structure and optical properties was primarily investigated in both experiment and theory. And the results demonstrate that changing the coordination mode from Cu–N to Cu–S has a significant effect on the electronic structure. This work will offer new insights into ligand engineering.